Respons Pertumbuhan Lada Perdu terhadap Pemberian Dosis Pupuk Kandang Sapi dan Mikoriza - Fahri Ali; Mochammad Arif Subechan; Bagus Prasetia (Politeknik Negeri Lampung, 2017)
Shrub pepper is a potential commodity to be cultivated under coconut trees of coastal sand. The problems are coastal sand generally not support plant to grow well, because of low of nutrition, organic matter, water holding capacity, soil fertility and high salinity. The aims of the research were to study the effect of mycorrhiza and cow manure doses on vegetatif growth of shrub pepper, and to study interaction between mycorrhiza and cow manure doses effect on vegetatif growth of shrub pepper. This experiment used Factorial Randomized Complete Blocks Design (RCBD) which consist 2 factors, first factor was doses of cow manure (P1= 5 kg.crop-1), (P2= 10 kg.crop-1) and (P3= 15 kg.crop-1). Second factor was doses of mycorrhiza (M0= without mycorrhiza/control), (M1= mycorrhiza 10 spore.crop-1) and (M2= mycorrhiza 20 spore.crop-1). Data obtained were analyzed with F test, and were continued with DMRT at 5 percent when significant. Results showed that mycorrhiza doses not affected the addition number of leaves, internodes and laterals, this can be explained there was endogenous mycorrhiza in the soil used based on colonization of mycorrhiza test (M0 21,07%; M1 23,84% and M2 16, 73%). The effect of cow manure doses to addition number of leaves, internodes and laterals gave the same response, it’s caused all cow manure doses can supply nutrition for vegetative growth of shrub pepper based on the content of chlorophyl (P1 89,20; P2 77,76 and P3 80,94 mg.l-1). There was no interaction between mycorrhiza and cow manure doses on all of observed variables. Keywords: Coastal sand, coconut, colonization, pepper, vegetative